Hydrocarbon pollution fixed to combined sewer sediment: a case study in Paris - Rocher, V.; Garnaud, S.; Moilleron, R.; Chebbo, G. (Chemosphere, 2004)
Over a period of two years (2000-2001), sediment samples were extracted from 40 silt traps (STs) spread through the combined sewer system of Paris. All sediment samples were analysed for physico-chemical parameters (pH organic matter content, grain size distribution), with total hydrocarbons (THs) and 16 polycyclic aromatic hydrocarbons (PAHs) selected from the priority list of the US-EPA. The two main objectives of the study were (1) to determine the hydrocarbon contamination levels in the sediments of the Paris combined sewer system and (2) to investigate the PAH fingerprints in order to assess their spatial variability and to elucidate the PAH origins. The results show that there is some important inter-site and intra-site variations in hydrocarbon contents. Despite this variability, TH and PAH contamination levels (50th percentile) in the Parisian sewer sediment are estimated at 530 and 18 mug g(-1), respectively. The investigation of the aromatic compound distributions in all of the 40 STs has underlined that there is, at the Paris sewer system scale, a homogeneous PAH background pollution. Moreover, the study of the PAH fingerprints, using specific ratios, suggests the predominance of a pyrolytic origin for those PAHs fixed to the sewer sediment. (C) 2003 Elsevier Ltd. All rights reserved.